PRODUCTION OF UNLEADED GASOLINE IN ASEAN COUNTRIES - A.S. Nasution; E. Jasjfi (Scientific Contributions Oil and Gas, 2006)
Worldwide crude supply is experiencing a mod- est trend towards heavier and high sulfur content. The Middle East, being traditionally the world's ma- jor oil exporting region, will continue to be the princi- pal supplier of lower quality crude's in the future", For the period 1992-2005, the average annual demand growth rate for light products ( gasoline, kero- sene, diesel oil) is higher than for residual fuel oil21, These data clearly show that the need will continue for converting additional bottom fraction into light products, by both thermal or catalytic conversions. The passage of the Clean Air Act Amendement of 1990 in the USA has forced American refineries to install new facilities to comply with stricter speci- fications for fuels such as gasoline and diesel oil such as Asia-Pacific, California Air Resources Board (CARB) and European Commission (EC) [3.4. 5). Various terms in the models address qualities and the gasoline blended such as benzene, total aromatics and olefin contents, RVP, the T90 of distillation range, sulphur content, and oxygenates content. Comparison of fue l specifications between ASEAN countries and reformulated fuels and typi- cal compositions of gasoline and gas oil components for production of commercial unleaded gasoline is included in this report.